2016
DOI: 10.4166/kjg.2016.67.5.245
|View full text |Cite
|
Sign up to set email alerts
|

Septic Shock in Pyogenic Liver Abscess: Clinical Considerations

Abstract: The presence of mental change, gas-forming abscess, and K. pneumoniae infection were independent predictors for septic shock in patients with PLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a previous report, 47 patients with PLA had markedly elevated CRP levels (mean, 27.2 mg/dL) (8). Cho et al reported that a high CRP level was a risk factor for septic shock in patients with PLA (41). Furthermore, in a Japanese retrospective multicenter study on 25 patients with EE (32 eyes), Todokoro et al reported that an elevated body temperature (64%), high serum CRP (96%), and leukocytosis (52%) were frequently observed (22).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, 47 patients with PLA had markedly elevated CRP levels (mean, 27.2 mg/dL) (8). Cho et al reported that a high CRP level was a risk factor for septic shock in patients with PLA (41). Furthermore, in a Japanese retrospective multicenter study on 25 patients with EE (32 eyes), Todokoro et al reported that an elevated body temperature (64%), high serum CRP (96%), and leukocytosis (52%) were frequently observed (22).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the various changes in liver abscess regarding its causes and risk factors, the management of PLA in Korea has not been updated correspondingly, and only a few studies on PLA in Korea since the mid‐2010s have been conducted. Since 2010, only six cohort results from a single centre have been reported 7,14‐18 . Therefore, it was impossible to calculate the population‐based incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2010, only six cohort results from a single centre have been reported. 7,[14][15][16][17][18] Therefore, it was impossible to calculate the population-based incidence. Moreover, prior to this study, there has been no population-based study in Korea.…”
mentioning
confidence: 99%
“…Klebsiella pneumoniae infection has been shown to be an independent predictor of the development of septic shock in initially stable patients with PLA 24 . A previous study by Cho et al .…”
Section: Discussionmentioning
confidence: 99%